Chocomake Broadrange / Hidayah Yahaya - Yahaya, Hidayah (2020)
Nowadays many young individuals and couples start business from their homes. This includes housewives and single mothers. As food and beverages are one of ‘easy selling’ items as they are daily consumption, business starters would choose to work on either home- based homemade cooking or repacking snacks. Chocolate is one of the best-selling sweets, however, most of these business starters lack in knowledge behind chocolat-ing. As such, they could be lacking in cooking skills and not confident in handling chocolate. In thisera of globalisation, people are busy with careers and spend more time on works and jobs.With striving technology and innovations, food technologists come up with fast foods to save time for prep to cooking their meals. Young couples tend to miss this particularly important skill which is cooking skills. On the other hand, raw cocoa-based ingredients are fairly rare to obtain in Malaysia unless you get them in bulks and steps in handling chocolate may require professional technique and insightful knowledge. For example, chocolates are overly sensitive and delicate especially when it comes to white chocolate, thus it must be handled with care and only be exposed to low heat to prevent it from disintegrating. As chocolate was not originated in Malaysia, we lack basic knowledge in handling chocolate.